Rejoiner to R. C. Boynton - Glueck, William F. (Academy of Management Journal, 1968)
A letter to the editor by Dr. William Glueck is presented as a rejoinder to R.C. Boynton's comments on his article ?Applied Organization Analysis,? from the September 1967 issue.